Answers

2014-07-24T16:35:05+08:00
(4 + x)³           >      the pattern is    (a + b)³  = a³ +3a²b + 3ab² + b³
                               this pattern should be remembered by heart
thus
(4+x)³  =      4³ +(3 . 4²x) +( 3 . 4x²) + x³
           =      64 + 48x + 12x² + x³
0
2014-07-25T15:43:12+08:00
(4+x)^3
4^3+3(4)^2+x+3(4)+x^2+x^3=the first term exponent should be 3,2,1 but the second term exponent is from 1,2,3.then add 3 to the second and third.
64+48x+12x^2+x^3= apply the said direction.
x^3+12x^2+48x+64= arrange your final answer.
0